2022
DOI: 10.1111/ors.12762
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐synthesis of qualitative data exploring the experience of living with temporomandibular disorders: The patients' voice

Abstract: Temporomandibular disorder (TMD) refers to a group of conditions that affect the temporomandibular joint and surrounding muscles. 1 Patients often report symptoms of pain in the jaw area and surrounding musculature, clicking sounds, alterations to the joint activities such as: deviation in the arc of movement, limitation to mouth opening, headache and earache. 2,3 TMD represents the most common cause of chronic pain in the orofacial region, 4 and is only behind headache and backache as reason for chronic pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Evaluation of the existing literature 8,13,15,17 including a recent meta‐synthesis of qualitative evidence 9 identified several themes relating to the experiences of patients with TMD. The three general themes listed below were used to support the recommendations suggested by patient participants in the Delphi process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Evaluation of the existing literature 8,13,15,17 including a recent meta‐synthesis of qualitative evidence 9 identified several themes relating to the experiences of patients with TMD. The three general themes listed below were used to support the recommendations suggested by patient participants in the Delphi process.…”
Section: Resultsmentioning
confidence: 99%
“…Following the Delphi process, the results of a recently published meta‐synthesis of qualitative data on the experiences of people living with TMD 9 and other relevant qualitative papers 13–15 identified by TMD clinicians and patients were used to ensure that any missed themes were identified from the literature and included in the recommendations. The recommendations were then distributed to all participants for their final approval.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like our study, past studies have found that patients with TMDs report somatic symptoms such as involuntary grinding, clenching, or chewing [ 19 24 ], jaw pain [ 25 ], jaw misalignment or dislocation, jaw noises including clicking and popping [ 25 30 ], headaches [ 31 – 33 ], and ear sensations, such as tinnitus [ 34 – 36 ], and deficits in physical function, such as the ability to eat and chew [ 20 , 22 ]. As in our study, affective symptoms including depression and anxiety were particularly prevalent among patients with TMD, especially among those with severe TMDs [ 37 44 ], as were effects on social function (e.g., restrictions in social interactions due to shame or embarrassment) [ 45 ], sleep quality [ 46 48 ], and sexual function (e.g., loss of sexual interest) [ 49 ].…”
Section: Discussionmentioning
confidence: 96%